Peripheral blood lymphocyte subset repertoires are biased and reflect clinical features in patients with dermatomyositis. (4th May 2019) - Sasaki, H; Takamura, A; Kawahata, K; Takashima, T; Imai, K; Morio, T; Kohsaka, H
Abstract : Objective : Dermatomyositis (DM) is an idiopathic inflammatory myopathy which often involves the lungs. DM is likely to be associated with aberrant T- and B-cell activation in the pathogenesis because of the proven effectiveness of T- and B-cell-targeted treatments. Assuming that the aberrant activation is reflected by biases in the lymphocyte subset repertoires, we aimed to elucidate these biases, especially in relation to clinical features of DM. Method : Based on the immunophenotyping standardized by the Human Immunology Project Consortium, untreated 13 DM patients, including seven patients with interstitial lung disease (ILD), and 18 age-matched healthy donors (HDs) were examined for proportions of peripheral blood lymphocyte subsets. Six DM patients were examined before and after successful induction of remission. Results : Naïve CD4 + T cells and naïve B cells were more abundant, while there were fewer naïve CD8 + T cells, central memory CD8 + T cells, effector memory CD4 + T cells, Th1 cells, Tfh cells, and memory B cells in DM patients than in HDs. When the patients were subgrouped according to the presence of ILD, the lymphocyte subset repertoires in the patients with ILD contributed to the statistical differences in all the biased lymphocyte subset proportions. After treatment, transitional B cells vanished and there was an increase in memory B cells. Conclusion : The lymphocyte subset repertoires in the DM patients were biased, and were associated with the presence of ILD and disease activity of DM.